Etika Bisnis Dalam Manajemen Bisnis Roti Maros Guna Mewujudkan Peningkatan Keharmonisan Sosial - Hidayat, Ihsan; Irwan Misbach; Syahruddin; Syahrir D Mallongi; Awaluddin (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2024)
Islam with its universal teachings has laid down the concept of human life so that it can run well, including business mechanisms in doing business. Maros is one of the cities that has entrepreneurs operating in the same field and type, namely Maros Roti Culinary. This research is descriptive qualitative research. The results of this research prove that Maros entrepreneurs really understand Sharia Business Ethics and they apply it in their business management. Five management principles are adapted to Sharia business ethics. The dominance of the same business in Maros Regency actually creates harmony between business people. They support each other through Public Transport Partners. Every driver who partners will get free drinks and food and get a bonus if each driver brings a lot of passengers to shop at the Maros Bakery. This is uniquely healthy competition for Maros Roti Entrepreneurs.